If a monkey jumps onto your school bus - Cochran, Jean M.; Morris, J. E. (Raynham Center, MA : Pleasant St. Press, 2008)
What do you do if a monkey jumps onto your school bus... or a hippo shows up for breakfast...or an elephant wants to run the bases at your ball game? There's only one way to find out! Rhythmic text and eye-catching illustrations charm the readers of this hilarious "guide" on what to do if the animals escape from your local zoo!
Keywords: Animals; Zoo animals; Zoo animals; Stories in rhyme